2019
DOI: 10.1177/1039856219839467
|View full text |Cite
|
Sign up to set email alerts
|

A sense of dread: affect and risk perception in people with schizophrenia during an influenza pandemic

Abstract: Objective: To explore the role of affect in risk perception and intention to adopt protective measures against pandemic swine influenza in people with schizophrenia. Methods: A cross-sectional study was conducted exploring the responses of 71 adults with schizophrenia and 238 adults attending general practice settings without schizophrenia. Participants completed a questionnaire that included items relating to: self-predicted affect (affective forecast) were they to contract swine influenza; perceived risk fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…Moreover, he was more concerned about others than himself, a manifestation possibly influenced by his former role as an ambulanceman. This observation may be in line with the previous reports that higher levels of concurrent anxiety in patients with schizophrenia correlated with lower perception of personal risk of infection with swine flu, although the reason for this effect is unclear (Maguire et al, 2019a). Patients with schizophrenia have also been shown to be less willing to get vaccinated and to adhere to social distancing during an influenza pandemic (Maguire et al, 2019b).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, he was more concerned about others than himself, a manifestation possibly influenced by his former role as an ambulanceman. This observation may be in line with the previous reports that higher levels of concurrent anxiety in patients with schizophrenia correlated with lower perception of personal risk of infection with swine flu, although the reason for this effect is unclear (Maguire et al, 2019a). Patients with schizophrenia have also been shown to be less willing to get vaccinated and to adhere to social distancing during an influenza pandemic (Maguire et al, 2019b).…”
Section: Discussionsupporting
confidence: 89%
“…It is reasonable to expect that media coverage of exceptional circumstances will influence the content of delusional thoughts, especially in crises like infectious disease pandemics or after assassinations. However, the number of studies addressing such issues is very limited; one such study carried out during the 2009 swine influenza pandemic indicated that patients with schizophrenia and a high level of predicted fear tended to judge their own risk of infection as higher (Maguire et al, 2019a). An interesting aspect of the current case is that in a highly interconnected world, our patient assumed a Chinese WhatsApp message had infected him.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they reported that higher levels of reported anxiety in those with schizophrenia were associated with a reduced likelihood of perceiving they were at substantive risk from swine flu. Maguire also reported a trend in perception towards people with schizophreniacompared to controls -being less likely to get swine flu (Maguire et al, 2019).…”
Section: Risk Perception In People With Psychosismentioning
confidence: 94%
“…Two papers were identified that examined perception of the risk of infection in people with psychosis (Iancu et al, 2005;Maguire et al, 2019). One study examined if the SARS epidemic caused anxiety and worry in 30 inpatients with a diagnosis of schizophrenia compared to a control group of 30 staff members in Israel where the virus was not endemic (Iancu et al, 2005).…”
Section: Risk Perception In People With Psychosismentioning
confidence: 99%
See 1 more Smart Citation